1991
DOI: 10.1007/bf00371617
|View full text |Cite
|
Sign up to set email alerts
|

The rhino mouse model: the effects of topically applied all-trans retinoic acid and CD271 on the fine structure of the epidermis and utricle wall of pseudocomedones

Abstract: The histological and ultrastructural effects following 3 weeks' topical treatment with two agents (all-trans retinoic acid and a new synthetic retinoid-like substance, CD271) were evaluated on the epidermis and the epithelial wall of the pseudocomedones in rhino mouse skin. The comedolytic effects of these drugs were similar, and consisted of a reduction of the utricular diameter, with normalization of follicular units. Morphological examinations revealed a hyperplastic response with an increase in the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 20 publications
2
16
1
Order By: Relevance
“…In the rhino mouse skin, the comedolytic effect of topically applied retinoids is characterized by a reduction in utricle diameter 5,29–31 . In the present study, tretinoin reproduced the comedolytic effect as previously reported 29 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the rhino mouse skin, the comedolytic effect of topically applied retinoids is characterized by a reduction in utricle diameter 5,29–31 . In the present study, tretinoin reproduced the comedolytic effect as previously reported 29 .…”
Section: Discussionsupporting
confidence: 89%
“…One of the comedolytic effects of adapalene has been considered to be an increased desquamation of the stratum corneum, 5,6 and tretinoin promoted desquamation in the present study. Unlike tretinoin, we observed orthokeratotic hyperkeratosis rather than desquamation with maxacalcitol.…”
Section: Discussionsupporting
confidence: 49%
“…Such an effect is maxi mum after 2 weeks of treatment, leading to disruption of both the stratum comeum layer and the follicular epithelium [4,6]. After 3 weeks of treatment, cells of the comeum lose cohesion, and scaling occurs [4,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Remnant sebaceous follicles are histologically reminiscent to retentional human acne lesions such as microcomedones. For that reason, the rhino mouse has extensively been used for comedone studies 14, 15. All procedures were performed according to protocols approved by the Nippon Medical School Subcommittee on Research Animal Care.…”
Section: Methodsmentioning
confidence: 99%